Respostas
respondido por:
1
2)
x²-x-6=0
a) 1
b)- 1
c)-6
∆=b²-4 a c
∆=(-1)²-4 * 1 * (-6)
∆=1 +24
∆=25
x=-b+-√∆/2*a
x= -(-1)+-√25/2*a
x=1+-5/2
x¹=1+5/2
x¹=6/2
x¹=3
x²=1-5/2
x²=-4/2
x²= -2
3)
2x²-8X+8=0 /2
x²-4X+4=0
a)1
b)-4
c)4
∆=(-4)²-4*1*4
∆=16-16
∆=0
x= -(-4)+-√0 / 2*1
x= 4+-0 / 2
x¹= 4+0/2
x¹= 4/2
x¹= 2
x²= 4-0/2
x²= 4/2
x²= 2
x²-x-6=0
a) 1
b)- 1
c)-6
∆=b²-4 a c
∆=(-1)²-4 * 1 * (-6)
∆=1 +24
∆=25
x=-b+-√∆/2*a
x= -(-1)+-√25/2*a
x=1+-5/2
x¹=1+5/2
x¹=6/2
x¹=3
x²=1-5/2
x²=-4/2
x²= -2
3)
2x²-8X+8=0 /2
x²-4X+4=0
a)1
b)-4
c)4
∆=(-4)²-4*1*4
∆=16-16
∆=0
x= -(-4)+-√0 / 2*1
x= 4+-0 / 2
x¹= 4+0/2
x¹= 4/2
x¹= 2
x²= 4-0/2
x²= 4/2
x²= 2
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás